2020
DOI: 10.1007/s11686-020-00292-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of Giardia duodenalis in Household Dogs and Cats from Poland

Abstract: Background Giardia duodenalis is a widespread protozoan parasite affecting humans and many species of animals, including dogs and cats. Due to its zoonotic potential, it is important to know the frequency of this parasite in companion animals. The aim of this study was to determine current epidemiological status of G. duodenalis in household dogs and cats. Methods In this study, 293 fecal samples from pet dogs and cats were collected from January 2017 to July 2019 and tested for G. duodenalis by PCR (using β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Age and gender were not statistically associated with G. duodenalis infection, comparably with previous data (Epe et al., 2010 ; Montoya et al., 2018 ; Piekara‐Stępińska et al., 2020 ; Tamponi et al., 2017 ); however, they are still present in different studies where younger cats (<6 months or <12 months of age) are considered at higher risk of positivity (Bouzid et al., 2015 ; Epe et al., 2010 ; Nagamori et al., 2020 ; Pallant et al., 2015 ; Sauda et al., 2019 ; Symeonidou et al., 2018 ; Tamponi et al., 2017 ; Zanzani et al., 2014 ). Regarding age, our findings could be affected by a bias due to the difficulty in recording accurate dates of birth in stray cats.…”
Section: Discussionsupporting
confidence: 90%
“…Age and gender were not statistically associated with G. duodenalis infection, comparably with previous data (Epe et al., 2010 ; Montoya et al., 2018 ; Piekara‐Stępińska et al., 2020 ; Tamponi et al., 2017 ); however, they are still present in different studies where younger cats (<6 months or <12 months of age) are considered at higher risk of positivity (Bouzid et al., 2015 ; Epe et al., 2010 ; Nagamori et al., 2020 ; Pallant et al., 2015 ; Sauda et al., 2019 ; Symeonidou et al., 2018 ; Tamponi et al., 2017 ; Zanzani et al., 2014 ). Regarding age, our findings could be affected by a bias due to the difficulty in recording accurate dates of birth in stray cats.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the detection rate of G. duodenalis in pet dogs mainly living indoors from Zhengzhou, central China, was similar to that reported in Brazil (6.9%)[ 28 ], and Poland (6.0%)[ 29 ]. However, it is lower than the prevalence of rural dogs in Argentina (44.4%)[ 30 ], and Italy (15%)[ 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Fewer studies have been done in cats, a recent meta-analysis found that 2.3% of cats tested positive for G. duodenalis, globally. European studies have found prevalence rates ranging from 5.9% to 20.5% in cats [19,20].…”
Section: Introductionmentioning
confidence: 99%